The Morphological Selection of Broken Plurals and Their Discursive Impact in Arab National Anthems/ الاختيار الصرفي لجموع التكسير واثره الخطابي في الأناشيد الوطنية العربية - Fatima Fuad Abdul Wahab Saeed; Raghad Jihad Abdul Hussein (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research examines the phenomenon of the conscious morphological selection of broken plural patterns in Arab national anthems, and analyzes their discursive role in shaping meaning and building emotional and ideological impact. It is based on the hypothesis that the selection by a poet or writer of a specific broken plural from among possible morphological alternatives is not arbitrary; rather, it carries discursive connotations that serve the purposes of the national text, such as reinforcing belonging, mobilizing efforts, embodying strength, and shaping collective memory. The research focuses on the official national anthems of selected Arab countries, considering them institutional discursive texts aimed at addressing a wide audience and entrenching shared values and identity. The research aims to inventory and classify the patterns of broken plurals used in a sample of Arab national anthems, and to analyze the semantic and discursive context in which each plural form appears. It also seeks to reveal the relationship between the original morphological denotation of the plural pattern. The research relies on a descriptive, analytical, and pragmatic methodology, combining: Morphological Analysis: To identify the patterns of broken plurals (e.g., af'āl, fi'āl, fu'ūl, fa'ala, fa'ālā, fa'ālil, etc.) and their denotations. Discourse Analysis: to study the plurals within their textual, social, and political context, and to link them to the objectives of the national discourse. To trace the semantic effect these plurals create in the mind of the recipient.